Starmera foglemanii sp. nov. and Starmera ilhagrandensis sp. nov., two novel yeast species isolated from ephemeral plant substrates. Issue 7 (25th July 2020) - Moreira, Juliana D.; Morais, Camila G.; Oliveira, Fernanda L. C.; Santos, Ana Raquel O.; Schlindwein, Clemens; Lachance, Marc-André; Rosa, Carlos A.
Abstract : Four isolates of two novel ascosporogenous species belonging to the clade Starmera were obtained from cactus tissues and rotting wood in Brazil. Results of analyses of the sequences of the ITS and D1/D2 domains of the large subunit rRNA gene indicated that the two isolates of the cactophilic species are related to Starmera caribaea and Starmera pilosocereana, yeasts that are associated with cacti and require an organic source of sulfur for growth. We propose the novel species Starmera foglemanii sp. nov. (CBS 16113 T ; MycoBank number: MB 834400) to accommodate these isolates. The other two isolates are phylogenetically related to Candida dendrica, Candida laemsonensis and Candida berthetii, also in the Starmera clade. The novel species name Starmera ilhagrandensis sp. nov. (CBS 16316 T ; MycoBank number: MB 834402) is proposed for this species.